2021
DOI: 10.3389/fcell.2021.722671
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hub mRNAs and lncRNAs in Atrial Fibrillation Using Weighted Co-expression Network Analysis With RNA-Seq Data

Abstract: Atrial fibrillation (AF)/paroxysmal AF (PAF) is the main cause of cardiogenic embolism. In recent years, the progression from paroxysmal AF to persistent AF has attracted more and more attention. However, the molecular mechanism of the progression of AF is unclear. In this study, we performed RNA sequencing for normal samples, paroxysmal AF and persistent AF samples to identify differentially expressed gene (DEG) and explore the roles of these DEGs in AF. Totally, 272 differently expressed mRNAs (DEmRNAs) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Six differentially expressed autophagy-related genes (BECN1, GAPDH, ATG7, MAPK3, BCL2L1, and MYC) and three immune cell subpopulations (T cells CD4 memory resting, T cells follicular helper, and neutrophils) were identified as the most significant potential regulators [ 34 ]. Yang et al (2021) and Qu et al (2021) also used WGCNA to identify hub mRNAs and non-coding RNAs in AF [ 35 , 36 ]. Comparing samples from subjects with and without AF, differentially expressed genes (DEGs) regulate multiple pathways, such as the modulation of vascular endothelial growth factor production and binding to the CXCR chemokine receptor.…”
Section: Diseasome and Non-coding Rnas In Af Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Six differentially expressed autophagy-related genes (BECN1, GAPDH, ATG7, MAPK3, BCL2L1, and MYC) and three immune cell subpopulations (T cells CD4 memory resting, T cells follicular helper, and neutrophils) were identified as the most significant potential regulators [ 34 ]. Yang et al (2021) and Qu et al (2021) also used WGCNA to identify hub mRNAs and non-coding RNAs in AF [ 35 , 36 ]. Comparing samples from subjects with and without AF, differentially expressed genes (DEGs) regulate multiple pathways, such as the modulation of vascular endothelial growth factor production and binding to the CXCR chemokine receptor.…”
Section: Diseasome and Non-coding Rnas In Af Pathogenesismentioning
confidence: 99%
“…Five hub modules were significantly negatively and positively correlated to the progression of AF. Besides the hub lncRNA–mRNA regulatory network, the hub protein–protein interaction (PPI) network was constructed and analyzed, showing the relevance of immune response signaling, such as leukocyte chemotaxis, macrophage activation, and positive regulation of α-β T cell activation in AF [ 35 ]. Qu et al (2021) identified two significant modules and two hub miRNAs (hsa-miR-146b-5p and hsa-miR-378a-5p) highly correlated with the AF phenotype and differentially expressed miRNAs and genes were predominantly enriched in inflammation-related functional items.…”
Section: Diseasome and Non-coding Rnas In Af Pathogenesismentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) are a heterogeneous class of noncoding RNAs that play an important role in gene regulation and are associated with a variety of genetic diseases and cancers ( Dangelmaier and Lal, 2020 ; Ramakrishnaiah et al., 2020 ). LncRNAs play important functions in many fields, mainly divided into epigenetic regulation, transcriptional regulation and posttranscriptional regulation, can transcriptionally regulate mRNA expression in cis or in trans, and can also bind to microRNAs as ceRNAs to regulate mRNA expression ( Yang et al., 2021 ). Over the past decade, there has been growing evidence that the genomes of many species are commonly transcribed, resulting in numerous LNcRNAs.…”
Section: Introductionmentioning
confidence: 99%